Has avian influenza virus H9 originated from a bat source? - Karamendin, Kobey; Kydyrmanov, Aidyn; Fereidouni, Sasan (Frontiers in Veterinary Science, 2024)
Influenza A viruses are important pathogens that can cause diseases with high mortality in humans, animals, and birds. Wild birds are considered the primary reservoir of all subtypes in nature. After discovering the H9 influenza A viruses in bats, questions arose about their potential to serve as an additional natural reservoir and about the priority of the viral origin: did the virus initially circulate in bats and then transmit to birds or vice versa? The H9 Influenza A viruses are of particular interest because fatal human infections caused by H5, H7, and H10 influenza viruses contained segments from H9 viruses. Recently, a novel subtype of influenza A virus (H19) was reported and closely related to the H9 bat influenza A virus by its hemagglutinin structure. The genome of novel H19 has revealed a mixed characteristic genomic signature of avian and bat influenza viruses. The time to most recent common ancestor (TMRCA) estimates have shown that the divergence time between the bat and avian H9-similar influenza virus occurred approximately at the end of the XVIII century. This article discusses the evolution and possible origin of influenza viruses of the H9 subtype isolated from bats and birds. The obtained data, along with the known data suggest that the primary reservoir of the H9 influenza virus is wild birds, from which the virus was transmited to bats. We hypothesize that the novel H19 could be a descendant of an intermediate influenza virus in the transition stage of spill-over from avian to bat hosts.